Just walk across the room simple steps pointing people to faith - Hybel, Bill (Grand Rapids, Mich. Zondervan, 2006)
Believers universally affirm that evangelism is a vital part of what God calls to do, but very few makes a practice of doing it. They feel awkward and ill-equipped either because they've never been trained, or because their lack of interaction with non-Christians prevents them from using and developing the skills they do have. Bill Hybels addresses these concerns and signals the next era in personal evangelism with just walk across the room. Drawing on fresh perspectives from the author's own experiences, as well as time tested and practical illustrations, just walk across room encourages and equips readers to routinely indicate spiritual conversations with those who don't know Christ. Publisher
Tuning our own harpstrings
Keywords: Witness bearing (Christianity)